Growth-suppressive effect of berberine on endometrial carcinoma cells: Role of mitochondrial and PI3K/Akt pathway. (August 2015) - Kuo, Han-Peng; Lee, Yi-Jen; Hsu, Chih-Yu; Lee, Shou-Lun; Hsu, Shih-Chung; Chuang, Tzu-Chao; Liu, Jah-Yao; Kuo, Chao-Lin; Ho, Chi-Tang; Kao, Ming-Ching
Highlights: BBR inhibits the cell proliferation of endometrial cancer cells. BBR induces the mitochondrial-mediated apoptosis and modulates PI3K/Akt signal transduction. BBR sensitizes the endometrial cancer cell line, AN3 CA to Taxol. Abstract: Berberine is an isoquinoline alkaloid and a popular dietary supplement in the US market for lowering blood glucose and managing a healthy lipid profile. The anti-tumour activity of berberine is also known. Endometrial cancer is a gynecological malignancy tumour. Our study demonstrated for the first time that berberine could be used to inhibit endometrial carcinoma cell proliferation in vitro and unveiled the relevant mechanisms. By flow cytometry, we found that berberine affected cell cycle distribution in endometrial cancer cells. Additionally, berberine could induce cell apoptosis through activation of the mitochondrial/caspase pathway. We further investigated berberine-mediated signal transduction in endometrial cancer cells and found that berberine engaged in the PI3K/Akt pathway, a cell proliferation- and cell cycle progression-related signalling pathway. Our results suggest that berberine could be used as a potential dietary supplement or functional food ingredient to prevent endometrial cancer.